Analisis Tinjauan Yuridis Terhadap Pembobolan Rekening Bank Digital Yang Dilakukan Pegawai Bank (Dalam Perspektif Hukum Perbankan Berdasarkan Studi Kasus Bank Jago 2023) - Wicaksana, Dika Hikmah; Ramadhan, Niko Rafael; Ramadhan, Aditya Rizky; Winata, Henry; Ardian, Muhammad Fadhil (Media Hukum Indonesia (MHI), 2024)
The case of account hacking by Bank Jago employees reveals major challenges in the digital banking security system. The method used in this study is based on literature review techniques using an empirical legal approach. This study analyzes the case from a legal perspective including Law Number 10 of 1998 concerning Banking, Law Number 27 of 2022 concerning Personal Data Protection, Law on Information and Electronic Transactions (ITE) Number 19 of 2016, and POJK No. 1/POJK.07/2013 concerning Consumer Protection in the Financial Services Sector. The results of the study were in the form of violations that occurred including abuse of authority, violation of bank confidentiality, and protection of personal data. The study shows the importance of strengthening regulations and internal supervision to prevent similar crimes in the digital banking era.